Libertad como responsabilidad: una elaboración axiomático-conceptual desde los aportes político-filosóficos de Hannah Arendt (2021)
This paper uses the documentary-bibliographic method to describe and develop, from an exegetical approach, crucial elements within the studies on Hannah Arendt,namely, the way in which it is possible to understand the freedom-responsibility relationship within the conceptual network that implies the theory of action andnatality in this author. In order to achieve this objective, the article is divided into three parts: on the one hand, in the first two sections, the concept of freedom andresponsibility are conceptually developed; on the other, a comparative-relational work is developed in which it is hoped to place both concepts in correspondencewith the rest of Arendt’s theoretical-conceptual scaffolding. Thus, a reinterpretation of this conceptual duo is sought from what the author postulates.